Demand Satisfaction as a Framework for Understanding Intermittent Water Supply Systems. Issue 7 (1st July 2019) - Taylor, David D. J.; Slocum, Alexander H.; Whittle, Andrew J.
Abstract: Nearly one billion people worldwide receive water through piped networks that are not continually pressurized and operate intermittently. The prevalence and persistence of these Intermittent Water Supplies (IWS) is surprising as this mode of operation induces water contamination and customer equity issues. Shortages of source water, customers' water demand, and leaking pipes are frequently cited as necessitating IWS. We propose a framework for understanding the persistence and operation of IWS. The supply system is represented by an average customer and a spatially averaged leakage rate. With this macroscopic hydraulic model, we relate customer demand satisfaction, source water availability, customer demand, and leakage. While this approach ignores the complexities of network topology, we find that the model approximates real systems well (calibrating to four intermittent reference networks achieved R 2 >0.94). The calibrated model is robust to moderate changes in demand and leakage (maintaining R 2 >0.83). Using the model, we show that the tipping point between satisfied demand and unsatisfied demand is a local optimum for utilities, which may explain the persistence of IWS. Beyond this point, the volume received by customers does not increase, but utilities must supply more water to the network. The generality of the proposed model enables its use when regulating and upgrading IWS. We demonstrate the latter by critiquing a performance‐based contract that was intended to improve an intermittent supply in India. Demand satisfaction has profound implications for hydraulics and human welfare. We propose the degree of demand satisfaction as a metric for evaluating IWS and for tracking the United Nations Sustainable Development Goal 6.1. Plain Language Summary: While most people get drinking water through underground water pipes, in some areas these pipes only provide water for a few hours each week. Globally, more than one billion people are served by these "intermittent water supply systems". In severely degraded systems, keeping pipes empty most of the time can reduce leakage and conserve source water, but it can also allow mud or sewage to enter through holes or cracks in the pipes, contaminating the water. This paper presents a simple model (an equation) that approximates how intermittent systems behave. The model suggests why intermittent operation is so common and highlights the challenges of improving such systems. The model relates hours of operation to factors such as source water supply, consumer demand, leakage, and if consumer demand is satisfied. The model implies that once consumer demand is satisfied, a system crosses a threshold and behaves differently: leakage, rather than demand, determines most of a system's water requirements. Measuring this threshold could identify systems that leave people thirsty and prioritize such systems for improvements. The model, therefore, provides new tools to support global commitments outlined in the United Nations' Sustainable Development Goal 6.1 and the Human Right to Water. Key Points: Without topology details, our proposed model of intermittent water supplies (IWS) matches closely with more complete network models While inadvisable, IWS provide utilities traditionally ignored, short‐term benefits (e.g., supply timing will change less due to drought) We propose a new demand satisfaction metric to quantify supply availability and help track Sustainable Development Goal 6.1 in IWS